Ecology and general biology - Thorp, James H.; Rogers, D. Christopher (Thorp and Covich's Freshwater Invertebrates, 2015)
Readers familiar with the first three editions of Ecology and Classification of North American Freshwater Invertebrates (edited by J.H. Thorp and A.P. Covich) will welcome the comprehensive revision and expansion of that trusted professional reference manual and educational textbook from a single North American tome into a developing multi-volume series covering inland water invertebrates of the world. The series entitled Thorp and Covich's Freshwater Invertebrates (edited by J.H. Thorp) begins with the current Volume I: Ecology and General Biology (edited by J.H. Thorp and D.C. Rogers), whic
Keywords: Freshwater invertebrates : Physiology; Freshwater invertebrates : Ecology